Housing Liquidity, Mobility, and the Labour Market - Head, Allen; Lloyd-Ellis, Huw (Review of Economic Studies, 2012)
We study the interactions among geographical mobility, unemployment, and home-ownership in an economy with heterogeneous locations, endogenous construction, and search frictions in the markets for both labour and housing. The decision of home-owners to accept job offers from other cities depends on how quickly they can sell their houses ( i.e. the houses' liquidity ), which in turn depends on local labour market conditions. Consequently, home-owners accept job offers from other cities at a lower rate than do renters, generating a link between home-ownership and unemployment both at the city level and in the aggregate. When calibrated to match aggregate U.S. statistics on mobility, housing, and labour flows, the model predicts that the effect of home-ownership on aggregate unemployment is small. When unemployment is high, however, changes in the rate of home-ownership can have economically significant effects.